Evaluation of quality of the children's menu in mall's restaurants - Caroline Barboza Duarte; Monica Glória Neumann Spinelli; Andrea Carvalheiro Guerra Matias (Sociedade de Pediatria de São Paulo, 2022)
Abstract Objective: To evaluate the quality of children's menus in restaurants located in shopping malls. Methods: To select the sample, restaurants from 30% of shopping malls in each region of the city of São Paulo were included and, after considering only one restaurant per chain, the total was limited to 151 restaurants, 30.2% of which (n=35) presented a children's menu. Data were collected through a form on Google Forms. Results: Of the restaurants with children's menu, 60% (n=21) were conventional restaurants and 40% (n=14) takeaway/fast-food. The large number of chains present in most visited malls showed a democratization of the way of eating, with popular and accessible menus, regardless of social status. Most of the analyzed foods were cooked (41.5%). Most preparations did not use grease in their preparation and there was a notable lack of fruit and vegetables (FV) (4%). Sweet desserts were offered in 11.4% of the places and 20% included gifts with meals. Conclusions: The scarce offer of children's menus, few options and low FV offer indicate the need for a new look at the development of children's menus and a greater integration between the possibilities of restaurants and the expectations of parents and children, in the challenge of integrating the relationship between the supply of new foods that promote healthier habits and their consumption.